Core Hopping of Bis-indole Derivatives to Identify an Effective Inhibitor for the Treatment of Bipolar Disorder - Priya, Sivasubramaniam Shanthi; Doss, Victor Arokia (Asian Journal of Biological and Life Sciences, 2020)
Bipolar disorder is found to be one of the crucial mental disorders with severe side effects. The suicide rate among patients with bipolar disorder is likely greater than with patients of major depression and up to 17%-19% of patients die by suicide. Various proofs identify that family of protein kinase C (PKC) can act as target in the treatment of BPD. Different medications for treating bipolar disorder may cause different side effects. Due to its higher severity of side effects there is a need for the development of novel drugs. In the present study, core hopping technique is employed to obtain a new compound with higher activity. X-ray crystal structure of PKC-ε protein was downloaded from Protein Data Bank (PDB ID: 1GMI). The target protein was obtained preprocessed for docking analysis. By using core-hopping method 21 novel structures were developed from bis-indole derivative. All the obtained compounds were subjected to molecular docking and molecular dynamics simulations. From the docking analysis a novel protocore 2-(3a,7a-dihydro-1Hindol- 3-yl)-3-(1H-indol-3-yl)-1,2,3,3a,4,6a-hexahydropyrazolo[3,4-d] [1,2,3]triazol-6-amine showed significantly higher binding energy (-12.8 kcal/mol) than the normal bis-indole derivative (-4.5 kcal/mol). From the molecular dynamics study, the protein-ligand complex were found to be highly stable and the structure of protein remains intact and undergoes no deformation after binding with the ligand. Thus, the novel compound obtained from core hopping technique can be used for the development of effective drugs for the treatment of bipolar disorder with lesser side effects.
Keywords: Bipolar disorder; Core hopping; Molecular docking; Molecular dynamics; Protein Kinase C